Synthesis and Crystal Structure of Novel 9-Styrylquinoline Substituted Acridines as Potential Inhibitors of Bacteria - Qi, Jia-Juan; Li, Shu-An; Zhang, Zhen-Ming; Wang, Ting; Zhao, Hong-Bo; Wang, Xuan; Yin, Fu-Jun (Asian Journal of Chemistry, 2015)
Novel compounds of 1,8-dioxodecahydroacridines were designed as potential inhibitors of bacteria and prepared via the multi-component reaction of styrylquinoline aldehydes, dimedone and ammonium acetate in high yield under mild condition. The structure of products has been characterized by X-ray crystal structural analyses, 1H NMR, IR, LC-MC and elemental analysis. The preliminary biological screening shows that target product display a certain degree of activity against the vibrio harveyi at 100 μg mL-1.